Penggunaan Metode Reading Aloud Untuk Meningkatkan Kemampuan Membaca Al Quran Pada Pembelajaran Al Quran Hadist di MI Sunan Drajad Betikharjo - Ainiyah, Ziana Dhurrotul; Fa’idah, Maulidya Lailatul (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
Qur’anic reading proficiency is a fundamental competency that must be mastered by elementary madrasah students. However, in practice, many learners still face difficulties in terms of fluency, accuracy, and the application of tajweed rules. To address this issue, the present study aims to examine the effectiveness of the Reading Aloud method in improving Qur’anic reading skills in the Qur’an Hadith subject at MI Sunan Drajad Betikharjo. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the Reading Aloud method enhances students’ technical skills, as reflected in reduced tajweed errors, improved articulation of letters, and increased fluency in reciting Qur’anic verses. Moreover, in the affective domain, students demonstrated greater self-confidence and willingness to read in front of teachers and peers. Thus, the Reading Aloud method proves to be effective as a learning strategy for the Qur’an Hadith subject, as it not only strengthens technical proficiency but also fosters students’ motivation and religious attitudes.